První partnerská soužití českých žen a mužů a rostoucí význam kohabitací - Anna Šťastná; Jana Paloncyová (Gender a Výzkum, 2011)
This study analyses the first partnerships of women and men in the Czech Republic and focuses on a comparison of family behaviour before and after the politically and socially important watershed of 1989. The authors investigate the type of first partnership (cohabitation versus marriage) and its timing. It can be assumed that significant changes in partnership behaviour exhibit a different pattern according to educational group, and moreover that differences in the timing and type of first partnership might also be expected from the point of view of gender. Given the increasing proportion of children born outside wedlock, attention is devoted to the impact of pregnancy and childbirth on partnership strategies. The data used in the paper are taken from the ‘Generations and Gender Survey’ carried out in the Czech Republic in 2008. The retrospective character of these data provides information on partnership careers in the context of other significant life events.